Enhancing research with Plenary Labs. (9th December 2016) - Sinha, Pawan; Bex, Peter; Kjelgaard, Margaret; Phillips, Flip
Abstract: The two most evident crises in the advanced research ecosystem in the USA are scarcity of funds and scarcity of jobs. We argue that both of these are outcomes of a flawed resource usage model and propose an alternative approach that can help alleviate these challenges. Named 'Plenary Labs', this approach is designed to act as a counterpoint to the traditional schema wherein each laboratory acts as a self-contained silo with a full complement of equipment and personnel to advance the principal investigator's research program. This schema results in redundancy across labs, as well as an inflated need for research assistants. Plenary Labs ameliorate both of these issues by consolidating equipment and technical manpower. By democratizing access to cutting edge resources, reducing the time and costs involved in experimental research, and reducing the imbalance between supply and demand for jobs, Plenary Labs have the potential to significantly enhance research.